2021
DOI: 10.1177/03795721211014778
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Breastfeeding and Child Overweight in Mexico

Abstract: Background: Globally, the prevalence of child overweight has increased over the past few decades. The largest burden of child overweight is identified among upper-middle-income countries, such as Mexico. Breastfeeding has been identified as one of the key affordable and modifiable maternal health behaviors protecting against child overweight. Objective: To examine the association between breastfeeding and child overweight while sequentially controlling for individual, household, and area factors in Mexican chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
10
0
10
Order By: Relevance
“…This study is in line with (Campos, Vilar-Compte, and Hawkins 2021) results showed that efforts to reduce child stunting in Mexico should include prenatal strategies aimed at preventing low birth weight offspring, especially among short women, households moderate to severe food insecurity, families with a higher number of children <5 years old, and indigenous people. Community.…”
Section: Resultssupporting
confidence: 89%
“…This study is in line with (Campos, Vilar-Compte, and Hawkins 2021) results showed that efforts to reduce child stunting in Mexico should include prenatal strategies aimed at preventing low birth weight offspring, especially among short women, households moderate to severe food insecurity, families with a higher number of children <5 years old, and indigenous people. Community.…”
Section: Resultssupporting
confidence: 89%
“…Related to child parenting, including early breastfeeding initiation, giving exclusive breastmilk for up to six months and continued with complement feeding up to two years will help babies and children to grow optimally. Another research [31] recommended the strategy to accelerate stunting prevention after delivery should include a multilevel strategy to support the mother to breastfeed their babies.…”
Section: Clean and Healthy Life Behaviourmentioning
confidence: 99%
“…Selain faktor kesehatan ibu, faktor yang juga berhubungan dengan kejadian stunting pada anak adalah faktor yang mempengaruhi pertumbuhan dan perkembangan anak, baik secara langsung ataupun tidak langsung. Adapun beberapa faktor yang mempengaruhi tumbuh kembang anak antara lain: riwayat memperoleh ASI eksklusif (Campos, Vilar-Compte, & Hawkins, 2021), riwayat kelahiran premature (Lestari, Villasari, & Kartika, 2020), riwayat BBLR (Putri, Salsabilla, & Saputra, 2022), penyakit infeksi (Triana & Haniyah, 2020) dan riwayat imunisasi (Fajariyah & Hidajah, 2020a) serta masih banyak yang lain.…”
Section: Kajian Pustakaunclassified